Stone Grinding Tools of the Northern Highlands of Jordan in Classical and Early Islamic Periods Case Study: Barsinia - el-Khouri, Lamia (Buried History: The Journal of the Australian Institute of Archaeology, 2011)
The paper describes and discusses the forty-two grinding stones found during the 2006 and 2007 excavation seasons at the site of Barsinia in northern Jordan. The basic types are identifi ed and while most of them are known from as early as the Neolithic period, one type, the rotary basalt quern, seems to be a new arrival during the Late Byzantine period.